Ex vivo comparison of the giant and transfixing knot in equine open and closed castration. (11th January 2016) - Comino, F.; Giusto, G.; Caramello, V.; Pagliara, E.; Bellino, C.; Gandini, M.
Summary: Reasons for performing study: In equine castration, application of a ligature on the spermatic cord to prevent complications such as haemorrhage and evisceration has been reported with controversial results. Characteristics of commonly used knots have not been studied. Objectives: To compare the modified transfixing and giant knots and the emasculator in open and closed equine castration techniques. Study design: Ex vivo experiment. Methods: A total of 144 testicles were randomly assigned to 2 groups for open or closed castration. Both groups were divided into 3 subgroups of 18 specimens each: emasculator only, emasculator plus giant knot and emasculator plus transfixing knot and the open castration group also contained 2 further subgroups of 18 testicles each: giant knot only and transfixing knot only. The length of suture material used was measured for each knot and the leaking pressure of the testicular artery measured using dye injection. In the closed castration group, parietal tunic tensile strength was measured with a tensiometer. Results: Leaking pressure was higher in open compared with closed castration, with no significant difference among subgroups. In the closed castration group, minimum leaking pressure for the emasculator plus transfixing knot and emasculator only subgroups were close to standard physiological arterial pressures. The giant knot required less suture material than the transfixing knot. Parietal tunic tensile strength was higher when ligatures were applied. Conclusions: The giant and transfixing knot techniques have comparable haemostatic capability and parietal tunic tensile strength, but the giant knot requires less suture material. In open castration, using the emasculator alone may produce adequate haemostasis. In closed castration, using the giant knot in combination with the emasculator increases the bursting pressure and possibly reduces the incidence of haemorrhage. In closed castration, application of a ligature may reduce the risk of evisceration.